CONTRIBUTION OF FISHERIES AND NON FISHERIES INCOME IN FISHERMEN HOUSEHOLD IN BAGAN DELI VILLAGE MEDAN BELAWAN SUBDISTRICT, MEDAN CITY, NORTH SUMATERA PROVINCE - Saputra Hanafi Rambe; Lamun Bathara; Trisla Warningsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in June 2018. This study aims to identify the types of fisheries and non-fisheries business work carried out by fishermen household members, analyzing the contribution of fisheries and non-fisheries business income to fishermen households. The method carried out in this study is a survey method, namely by conducting observations and direct reviews and collecting samples taken 10% of the total population with simple sampling random sampling. The results of this study indicate that the types of activities carried out by members of fishing households in fisheries and non-fisheries businesses.      The types of fisheries and non-fisheries business carried out by fisherman household members in Bagan Deli Village, Medan Belawan Sub-District, Medan City, North Sumatra Province are in fisheries businesses, such as factories, maintaining ships, selling fish, drying salted fish, repairing nets, boat men , while the work carried out by fishermen from non-fisheries businesses is like Building Workers, Coffee Shops, Ojek, Security Guards, Trading, Keep Cellphones, Maintain Shops, Take Care of Pharmacies, Car Drivers, Sell Gasoline, Public Transportation Drivers, Building Workers and Elementary Workers. The average income of a fishery business is IDR. 2,785,400 with contributions as much as (56%), and the average income from non-fishery businesses is IDR. 2,221,667  with a contribution of (44%).Keywords: Contributions, non-fisheries, income of fishermen house holds